'To the Nomadic State': riding the rails to globalisation in Hawthorne's The House of the Seven Gables. Issue 1 (2nd January 2020) - Hardack, Richard
ABSTRACT: In this artice, I explore how Hawthorne addresses the relationship between spatial and social mobility in his depictions of railroads, and I partly focus on the chapter in The House of the Seven Gables in which Clifford and Hepzibah travel by train. Clifford's reaction to the new spatialisation the railroad augured encapsulates one of the novels' central concerns – how travel and mobility will eviscerate, or emancipate us from, social bonds. For Hawthorne, the not so celestial railroad is an emblem not only of modernity, but secularisation, class destabilisation, and what we might see as a form of proto-nomadisation. By nomadisation, I refer to some of the spatial effects of globalisation at this stage of its development, in which local homes, traditions, economies, and identities are increasingly supplanted by interconnected, uprooted, and transient identities, and space and time become increasingly entangled and compressed. Toward the end of the article, I address the connection between nomadism and the loss of home – emblematised by the railroad – and the annihilation of space through time. I propose that in House Hawthorne stages a series of contests that gauge the material and ontological implications of rail travel in ways that display his ambivalence about both progress and tradition. At stake is whether the railroad, which connects all places at once (replacing nature), undermines the fixity of real property (houses that should be homes). Partly because land is neither fungible nor movable, Clifford avers that 'what we call real estate – the solid ground to build a house on – is the broad foundation on which nearly all the guilt in the world rests.' By the end of the 1840s, however, that solid ground or immovable object had begun to meet the unstoppable forces that the railroad represented.